Main reasons for organ donation in a sample from Campinas/SP - Boteon, Yuri Longatto; Santos Junior, Luiz Carlos dos; Marchiani, Nathalia Carolina Perruche; Azevedo, Keila Domingos de; Boin, Ilka de Fatima Santana Ferreira; Pereira, Maria Isabel Warwar; Sá, Flavio Cesar de (Brazilian Journal of Transplantation, 2010)
Introduction: The waiting time for an organ is long, and many individuals die before surgery. On the other hand, only a small percentage of potential donors are effectively performed. The main reason for such paradox is the families’ disagreement on the organ donation. Purpose: to assess the relevance of the main reasons raised in the literature whether to donate or not organs, and the factors that interfere in such a choice. Methods: This is a cross section study based on answers pertained to a structured questionnaire with socio-demographic questions and also some questions about the reasons whether to donate or not. One-hundred and forty-nine subjects were interviewed; the statistical analysis was performed by analyzing the frequency tables, analytical description of continuous variables and applying the qui- square on the related risk correlating donor / non-donor groups to the variables. Statistic significance level adopted was 0.05. Results: It was found that forty-one point two percent of individuals were willing to the organ donation; the associated factors were higher education level and knowledge on the organ donation issues. Intention to donate organs to save lives was the most relevant factor that contributed for the organ donation. Conclusions: Along with higher education level, the knowledge on the organ donation and altruistic issues were elements favorable to the organ donation.